Cover Image, Volume 67, Issue 5. Issue 5 (30th March 2018) - Jeong, Keuk‐Min; Li, Yuheng; Yoo, Dae‐Geon; Lee, Nam‐Kyoung; Lee, Hyeok‐Gi; Ando, Shinji; Ha, Chang‐Sik
Abstract : The cover image, by Keuk‐Min Jeong et al., is based on the Research Article Effects of crosslinking agents on the physical properties of polyimide/amino‐functionalized graphene oxide hybrid films, DOI:10.1002/pi.5555 . Abstract : The cover image, by Keuk‐Min Jeong et al., is based on the Research Article Effects of crosslinking agents on the physical properties of polyimide/amino‐functionalized graphene oxide hybrid films, DOI:10.1002/pi.5555 .